Expression of Progesterone Receptor Membrane Component 1 (PGRMC1) in Follicular and Luteal Tissues in Goats – Effect of Short-term Concentrate Supplementation - Mohammed, N. H.; ShikhMaidin, M.; Yong, C. S. Y.; Ling, K. H.; Martin, G. B. (Tropical Animal Science Journal, 2025)
This study evaluated the effects of short-term supplementation with concentrate on ovulation rate, plasma progesterone concentrations and gene expression for Progesterone Receptor Membrane Component 1 (PGRMC1) in ovarian tissues of Boer goats. Twenty females were allocated to two groups: 1) Control, receiving a maintenance diet consisting of 70% Napier grass plus 30% concentrate (4.45 MJ/day); 2) Supplemented, receiving twice their required metabolizable energy for maintenance by adding extra concentrate (8.90 MJ/day). The dietary treatments were applied for 25 days, beginning 5 days before (Day 5) CIDR removal (Day 0). On Day 19, the ovulation rate was estimated by trans-rectal ultrasonographic scanning. Blood was sampled for progesterone (P4) analysis every 2 days, from Days 9 to 27. On Day 27, the level of expression of PGRMC1 was assessed in follicles and corpora lutea. The ovulation rate was not affected by treatment (Control 1.00 ± 0.24; Supplemented 1.25 ± 0.25). Over Days 13 to 27, plasma P4 concentrations were significantly (p